Kotlin standard library cookbook : master the powerful Kotlin standard library through practical code examples - Urbanowicz, Samuel (Packt Publishing, 2018)
This book explores the valuable standard libraries, showing you how to use them to write succinct code. Filled with short and easy-to -follow solutions, you'll see how to get optimal performance from your Kotlin code.